Recovering the margins of American religious history: the legacy of David Edwin Harrell, Jr - Waldrep, B. Dwain; Billingsley, Scott (Religion and American culture, 2012)
David Edwin Harrell, Jr. : American religious historian / Samuel S. Hill -- Elijah's never-failing cruse of oil : David Harrell and the historiography of America's Pentecostals / James R. Goff, Jr. -- David Edwin Harrell, Jr. and the history of the Stone-Campbell tradition / Richard T. Hughes -- David Edwin Harrell, Jr. and the broadening of Southern religious studies / Charles Reagan Wilson -- The Midas touch : Kenneth E. Hagin and the Prosperity Gospel / Scott Billingsley -- Rock fights, quarantines, and confessionals : B.C. Goodpasture, The gospel advocate, and keeping order in Churches of Christ / John C. Hardin -- Northern millenarian fundamentalism in the South, 1900-1950 / B. Dwain Waldrep -- Conclusion : the very civil convictions of Ed Harrell / Beth Barton Schweiger